Production of Plastic Cement Concrete from PVC Waste - Iram Juma Ibrahim Al Kindi,; M. Geetha Devi,; Mohammed Al Abri,; Soleen Al Hasan,; Eman Muhye Adeen Muhye Al Hatali,; Aravind N, (Fine Chemical Engineering, 2021)
The disposal of plastic wastes into the environment is a serious concern due to its limited biodegradability and production in excess quantity. The accumulation of enormous volumes of plastic waste is considered to be a major pollution problem and it is essential to find an alternate method to address such issues in an environmental-friendly and cost-effective way. The current research focused on the production of plastic cement concrete from waste polyvinyl chloride (PVC) generated from a polymer processing industry in varying proportions, and to modify the concrete properties. Polyvinyl chloride was partially replaced with Ordinary Portland Cement (OPC) by varying its compositions from 15% to 35% by weight (i.e. 15%, 20%, 25%, 30% and 35% OPC). The curing period was kept for 7 days after casting process. The produced plastic cement concrete was tested for compressive strength through Universal Testing Machine (UTM). Density and water absorption tests were also carried out on hardened concrete to assess the application of plastic cement concrete as a building material. The other characterization techniques employed are Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD) analyses. It was observed that up to 15% by weight of polyvinyl chloride could be replaced with OPC which exhibited higher compressive strength (19.25 MPa) compared to other mix proportions. A maximum density of 2.051 g/cm3 was obtained at a concrete mix composition corresponding to 25% replacement. The maximum water absorption percentage (5.86%) was observed at 35% plastic waste replacement. The studies demonstrate that the waste plastic material is considered to be a cost-effective, viable and sustainable way of reducing the environmental pollution.